Implementasi Konsep 5S Pada Industri Baja di Indonesia - Rahmat Putra Zulyet; Bayu Hari Nugroho; Dwinita Chika Finira; Nurfitri Rahmawati (Universitas Mercu Buana, 2019)
To continue to be an industrial company producing large expenditure capacity, it is necessary to have a good and comfortable working area for workers who work. However, in the current situation, there are several types of work areas and inadequate working equipment conditions in order to maintain good working conditions and better production results. This study aims to evaluate the cleanliness, discipline of the work environment in a steel industry company located in Banten Province. The 5S method is one of the uses to improve and create a comfortable work style. The implementation that has been carried out is that unused equipment has been separated and disposed of as well as grouping of necessary equipment, a special room (tool room) has been made for equipment storage, a tool room and a table for each equipment have been made, updates have been made to floor markers, procurement of trolleys with the aim of wasting working time, special places and signs for oil storage have been made, set cleaning activities, the operator is obliged to clean the machines after that have been used and every Friday morning working from 08:00 - 10:00.